Digital India Initiative: The Road Towards Sustainable Development - Keerthana P Girijan (Journal of Communication, Media, and Development Studies (COMMEDIES), 2024)
As the world moves towards becoming technologically empowered, local governing bodies seek effective ways to promote sustainable, affordable, and citizen-centric digital technologies to meet the growing demands of the public and for the Government services to reach out to more people. The Digital India initiative of the Indian Government has been engaging and transforming lives and livelihoods at the grassroots through technological interventions. The platform has been able to create a sense of unified response in every part of the country to pandemics, calamity, and crisis; it has contributed to the sustainable well-being of the people in the country. Through the transformative initiatives of Digital India, India as a country has been directly as well as indirectly been able to contribute to the United Nations Sustainable Development Goals. This paper discusses how technology, particularly the Digital India initiative, has been effectively changing the lives of its citizens, and, at the same time contributing to Agenda 2030